End winding cooling in electric machines - Micallef, Christopher (2006)
The fluid flow field and temperature distribution within the end region of a Totally Enclosed Fan Cooled (TEFC) induction motor have been investigated both experimentally and using Computational Fluid Dynamics (CFD) techniques, in order to improve the thermal performance. The flow field and the distribution of heat transfer coefficients over the end windings and internal surfaces (mainly frame and end shield) are characterised for a typical end region configuration. This is then used as a base case in order to investigate the impact configuration changes have on the fluid flow field and heat transfer characteristics in the end region of TEFC induction motors. Common parameters governing the flow field inside the end region are varied, allowing recommendations for improved design and further research recommendations to be made. CFD techniques are successfully applied to model the end region, including the copper where the heat generated is a function of temperature. Through these numerical techniques a good understanding of the flow field was made possible which enabled the author to propose and test configuration changes which improve the heat transfer characteristics in the region. These changes were validated experimentally.